2006
DOI: 10.1002/prep.200600065
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Two Potential Energetic Azido Esters

Abstract: Two new energetic azido esters named 1,3‐bis(azidoacetoxy)‐2‐azidoacetoxymethyl‐2‐ethylpropane (I) and 1,3‐bis(azidoacetoxy)‐2,2‐bis(azidomethyl)propane (II), have been synthesized and characterized by IR, NMR and Elemental Analysis. Thermal studies revealed that azido esters I and II are stable up to 180 °C and their glass transition temperatures are −47 °C and −52 °C, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…Then, it could be concluded that ABAMPA is much insensitive than TAP‐Ac, which was also confirmed by the friction sensitivity (FS) results of ABAMPA (324 N) and TAP‐Ac (54 N) . Besides, the impact and friction sensitivities of ABAMPA were comparable if not less than some previously reported azido ester plasticizers, such as BAEM, BAEG and 1,5‐diazido‐3‐nitrazapentane (DIANP) ,,. Therefore, the insensitivities toward impact and friction of ABAMPA is proved experimentally.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Then, it could be concluded that ABAMPA is much insensitive than TAP‐Ac, which was also confirmed by the friction sensitivity (FS) results of ABAMPA (324 N) and TAP‐Ac (54 N) . Besides, the impact and friction sensitivities of ABAMPA were comparable if not less than some previously reported azido ester plasticizers, such as BAEM, BAEG and 1,5‐diazido‐3‐nitrazapentane (DIANP) ,,. Therefore, the insensitivities toward impact and friction of ABAMPA is proved experimentally.…”
Section: Resultssupporting
confidence: 68%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 were comparable if not less than some previously reported azido ester plasticizers, such as BAEM, BAEG and 1,5-diazido-3-nitrazapentane (DIANP). [4,12,[21][22][23][24] Therefore, the insensitivities toward impact and friction of ABAMPA is proved experimentally.…”
Section: Thermal Decomposition and Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental data of the heat of formation of 40 organic azido compounds [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] were used for construction and validation of the proposed models. Table 2 illustrates the experimental data of 33 different azido compounds with various molecular structures, which were used as training set.…”
Section: Methodsmentioning
confidence: 99%
“…The glass transition temperature (T g )o fs ome mixtures of polymer and plasticizer for the effect of monomer mixture on the T g 's of copolymers systemsh ave been studied in the literature [12,[46][47][48][49][50][51].S ince, the molecular flexibility of the plasticizer is an importantm echanism for altering the brittleness of polymers via plasticization, the implication of this observation can be obtainedf rom the deviations of T g .I n the presented study,t he effect of adding plasticizer was observedi nt ermso fT g of polyNIMMO, which again indicates the compatibility of plasticizers with polyNIMMO. Maximum lowering of T g (À52 8C) was observed in the cases of BuNENA and DEGDN, where as BDNPAh as shown minimum lowering of T g at À38.85 8C ( Figure 2).…”
Section: Thermal Studiesmentioning
confidence: 98%